Chapter 10 Digital skills and application use among Finnish home care workers in the eldercare sector - Rantala, Eero (Taylor & Francis, 2022)
This chapter explores the role digital skills, interest in technology, and social support have in home care workers' use of digital applications at work. The empirical research is based on the 2019 University of Jyväskylä survey study on eldercare work (N = 6,903), drawn from the members of four majors trade unions in Finland. In this chapter, a sub-sample of home care workers (n = 1,398) is used in the analyses. Structural equation models are used to estimate the direct and indirect effects of available technology support, digital skills, and interest in technology on the actual use of various digital applications at work. According to the results, technology support has no direct effect on the use of digital applications. However, technology support seems to increase interest in technology and improve digital skills, which in turn promotes the use of digital applications. The availability of technology support appears as a crucial facilitator for home care workers' digital agency at work.